Cultural Variation in the Focus on Goals Versus Processes of Actions. (June 2013) - Miyamoto, Yuri; Knoepfler, Christopher A.; Ishii, Keiko; Ji, Li-Jun
Everyday actions (e.g., riding a bike) can be described in ways that emphasize either the goals of the action by adapting a higher level identification (e.g., getting exercise) or the processes of the action by adapting a lower level identification (e.g., pedaling). In Studies 1 and 2, we demonstrate cultural differences in focusing on the process or goal of actions at the individual level: Americans are more likely than Japanese to focus on the goal (rather than the process) of actions. Study 3 recruited Chinese participants in addition to American and Japanese participants and found that cultural differences in action identification are partly explained by cultural differences in self-consistency. Study 4 further showed cultural differences at the collective level: American media presents more goal-oriented information and less process-oriented information than does Japanese media. These findings highlight the role of culture in shaping how people attend to different aspects of actions.